Ketogenic metabolic therapy in the remission of chronic major depressive disorder: a retrospective case study - Laurent, Nicole; Bellamy, Erin L.; Hristova, Donika; Houston, Ally (Frontiers in Nutrition, 2025)
BackgroundThere is limited evidence describing the use of ketogenic metabolic therapy (KMT), also known as a ketogenic diet (KD), to achieve full remission of treatment-resistant major depressive disorder (MDD) in real-world clinical settings. This case study examines a 47-year-old woman with lifelong treatment-resistant MDD who achieved complete remission of depressive symptoms and improved functioning through a ketogenic diet.MethodsThe patient engaged in KMT with a 1.5:1 macronutrient ratio under the supervision of a treatment team consisting of a medical professional, psychotherapist, and ketogenic-informed nutrition professional through an online program that provided both individual and group support. Interventions included dietary modifications, micronutrient supplementation, and participation in a group coaching program. Outcomes were assessed using validated tools for symptom severity, including PHQ-9 for depression and GAD-7 for anxiety, at baseline, 2 months, and 4 months post-intervention. Qualitative data on patient experiences and functional improvements were also collected.ResultsThe patient achieved remission of MDD within 8 weeks of initiating KMT, with PHQ-9 scores decreasing from 25 (severe depression) at baseline to 0 at 2- and 4-month assessments. GAD-7 scores decreased from 3 (minimal anxiety) to 0 over the same period. Qualitative findings revealed significant improvements in emotional regulation, energy levels, and cognitive function.ConclusionThis case study demonstrates the potential of KMT as a non-pharmacological intervention for achieving full remission in treatment-resistant MDD. These findings suggest further research to evaluate feasibility, efficacy, and broader applicability in diverse clinical settings.